Boosting regulatory T cell function for the treatment of autoimmune diseases – That’s only half the battle! - Schlöder, Janine; Shahneh, Fatemeh; Schneider, Franz-Joseph; Wieschendorf, Björn (Frontiers in Immunology, 2022)
Regulatory T cells (Treg) represent a subset of specialized T cells that are essential for the regulation of immune responses and maintenance of peripheral tolerance. Once activated, Treg exert powerful immunosuppressive properties, for example by inhibiting T cell-mediated immune responses against self-antigens, thereby protecting our body from autoimmunity. Autoimmune diseases such as multiple sclerosis, rheumatoid arthritis or systemic lupus erythematosus, exhibit an immunological imbalance mainly characterized by a reduced frequency and impaired function of Treg. In addition, there has been increasing evidence that – besides Treg dysfunction – immunoregulatory mechanisms fail to control autoreactive T cells due to a reduced responsiveness of T effector cells (Teff) for the suppressive properties of Treg, a process termed Treg resistance. In order to efficiently treat autoimmune diseases and thus fully induce immunological tolerance, a combined therapy aimed at both enhancing Treg function and restoring Teff responsiveness could most likely be beneficial. This review provides an overview of immunomodulating drugs that are currently used to treat various autoimmune diseases in the clinic and have been shown to increase Treg frequency as well as Teff sensitivity to Treg-mediated suppression. Furthermore, we discuss strategies on how to boost Treg activity and function, and their potential use in the treatment of autoimmunity. Finally, we present a humanized mouse model for the preclinical testing of Treg-activating substances in vivo.